Effect of Intermediate Esters Towards Boundary Lubricity of Palm Methyl Ester - Lee, Chiew Tin; Low, Hong Lian; Lee, Mei Bao (Penerbit UTM Press, 2023)
Mechanism of methanolysis, using vegetable oil, methanol, and base-catalyze, is generally used to produce methyl ester. This method is also utilized for the kinetic study of the transesterification process based on the formation of fatty acid methyl esters to differentiate among the intermediate esters (e.g., triglyceride, diglyceride, monoglyceride, methyl esters). In the present study, the effect of intermediate ester content of palm oil transesterified with methanol, using potassium hydroxide as base-catalyze, was investigated. The operating conditions of transesterification used were the molar ratio of oil to methanol (1:7), the concentration of catalysis (1.0 wt% based on palm oil) with fixed reaction temperature of 55°C at reaction times of 0.5 and 60 minutes. A kinetic model was then adopted to determine the concentra tion of each intermediate esters. Boundary frictional analyses were conducted using lateral force microscopy (LFM) with different tip sliding velocities and applied normal loads. The experimental results obtained demonstrated that high triglyceride content exhibited better boundary frictional properties across tested tip sliding velocities and normal loads.